2010
DOI: 10.1158/0008-5472.can-10-0820
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency of Splicing Factor 1 Suppresses the Occurrence of Testicular Germ Cell Tumors

Abstract: Testicular germ cell tumors (TGCT) originate from germ cells. The 129-Ter and M19 (129.MOLF-Chr19 consomic) mouse strains have extremely high incidences of TGCTs. We found that the expression levels of Sf1-encoded splicing factor 1 (SF1) can modulate the incidence of TGCTs. We generated mice with inactivated Sf1. Sf1 null mice (Sf1−/−) died before birth. Mice with one intact allele of Sf1 (Sf1+/−) were viable but expressed reduced levels of Sf1. When Sf1-deficient mice (Sf1+/−) were crossed to the 129-Ter and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0
4

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 52 publications
3
26
0
4
Order By: Relevance
“…Despite this protective effect on TGCT formation, all mutant males are sterile due to a complete germ cell deficiency (R. Zhu et al, 2010). This phenotype is similar as those observed in the {Ter/Ter; Bax -/ + } males suggesting a common pathway involving both SF1 and BAX on PGC deficiency in 129-Ter/Ter mice.…”
Section: Gene-gene Interactionssupporting
confidence: 63%
See 2 more Smart Citations
“…Despite this protective effect on TGCT formation, all mutant males are sterile due to a complete germ cell deficiency (R. Zhu et al, 2010). This phenotype is similar as those observed in the {Ter/Ter; Bax -/ + } males suggesting a common pathway involving both SF1 and BAX on PGC deficiency in 129-Ter/Ter mice.…”
Section: Gene-gene Interactionssupporting
confidence: 63%
“…Liu et al, 2001). Interestingly, Sf1 deficiency (heterozygous Sf1 -/ + ) in 129-M19/+ males reduces the incidence of TGCTs (R. Zhu et al, 2010), suggesting that Sf1 may be one of the TGCT enhancer genes on chromosome 19. D19Bwg1357e is a predicted gene down-regulated in the gonads of MOLF strain mice (R. Zhu et al, 2007).…”
Section: -M19mentioning
confidence: 99%
See 1 more Smart Citation
“…The five QTLs that were detected showed pervasive epistatic effects depending on the genetic constitution of the congenic strain. Subsequent expression studies with these congenic strains revealed strong candidate genes for several of these QTLs (Zhu et al 2010). Presumably, the large number of susceptibility genes and their interactions account for the broad QTL localization in the CSS cross.…”
Section: Strategies To Locate Qtlsmentioning
confidence: 99%
“…These discoveries include the splicing factor 1 in control of TGCT susceptibility (Zhu et al 2010); solute receptor Slc35b4 as a regulator of diet-induced obesity, insulin resistance, and gluconeogenesis (Yazbek et al 2011); the TNNi3 kinase Tnni3k , fucose-1 phosphate guanylyltransferase Fpgt , or H28 genes in control of viral myocarditis (Wiltshire et al 2011); tomosyn-2 (syntaxin binding protein 5-like, STXBL5L ) as a negative regulator of insulin secretion (Bhalnagar et al 2011); lymphocyte antigen 6 complex, locus A Ly6a as a regulator of novelty responsiveness (de Jong et al 2011); transcription factor AP2 alpha Tcfap2a in control of voluntary physical activity through a dopaminergic pathway (Yang et al 2012); a long noncoding RNA (Rubie) upstream of Bmp4 in vestibular development (Roberts et al 2012); and the voltage-gated potassium Cntnap2 gene in control of diet-induced obesity (Buchner et al 2012). These early results clearly show the efficacy of gene discovery with CSSs.…”
Section: Strategies To Locate Qtlsmentioning
confidence: 99%